2007
DOI: 10.1103/physrevlett.99.196403
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Insulator Transitions in the Periodic Anderson Model

Abstract: We solve the Periodic Anderson model in the Mott-Hubbard regime, using Dynamical Mean Field Theory. Upon electron doping of the Mott insulator, a metal-insulator transition occurs which is qualitatively similar to that of the single band Hubbard model, namely with a divergent effective mass and a first order character at finite temperatures. Surprisingly, upon hole doping, the metalinsulator transition is not first order and does not show a divergent mass. Thus, the transition scenario of the single band Hubba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 18 publications
(17 reference statements)
2
40
0
Order By: Relevance
“…In the dynamical mean-field theory ͑DMFT͒, the self-energy ⌺͑͒ of the impurity site and the effective medium is obtained self-consistently. 20,21 Alternatively, the effective medium can be described by adjustable parameters as in the extended cluster model. [22][23][24] This model was already applied to high-T C superconductors, 22 colossal magnetoresistance materials, 23 and Mott-Hubbard systems.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…In the dynamical mean-field theory ͑DMFT͒, the self-energy ⌺͑͒ of the impurity site and the effective medium is obtained self-consistently. 20,21 Alternatively, the effective medium can be described by adjustable parameters as in the extended cluster model. [22][23][24] This model was already applied to high-T C superconductors, 22 colossal magnetoresistance materials, 23 and Mott-Hubbard systems.…”
Section: Calculation Detailsmentioning
confidence: 99%
“…Investigations of these systems have suggested that a crucial control parameter to determine the degree of correlation is the filling of the correlated d orbitals [13][14][15][16][17][18][19], which however does not generally correspond to an integer total number of electrons per site. Moreover, simplified models for these systems display seemingly contradictory results, where the hybridization between a correlated electronic band and a wide band of non-interacting electrons can either forbid [20] or allow [21][22][23][24] In this work we provide an answer to some of these questions. We study the conditions under which a Mott transition takes place, and what are its properties in a a simple, yet generic, model which captures the essential ingredients of the collective behavior of strongly correlated d-electrons hybridized with a band of noncorrelated electrons.…”
mentioning
confidence: 99%
“…The doping driven metal-insulator transition (MIT) in the paramagnetic Mott-Hubbard insulator was the focus of our recent study [16]. The main finding was a qualitatively different scenario for the electron or hole driven transitions.…”
mentioning
confidence: 99%
“…On the other hand, there is also a competing ferromagnetic interaction induced by hole doping. The doped holes need to delocalize to lower their kinetic energy, but they are subject to a strong on-site magnetic binding to the local moments [16]. Therefore, in order to hop, they need the local moments of the neighbor sites to have the same magnetic orientation as the one in its current site.…”
mentioning
confidence: 99%
See 1 more Smart Citation